Characteristics of Quinolone Resistance in Escherichia coli Isolates from Humans, Animals, and the Environment in the Czech Republic - Röderova, Magdalena; Halova, Dana; Papousek, Ivo; Dolejska, Monika; Masarikova, Martina; Hanulik, Vojtech; Pudova, Vendula; Broz, Petr; Htoutou-Sedlakova, Miroslava; Sauer, Pavel; Bardon, Jan; Cizek, Alois; et al. (Frontiers in Microbiology, 2017)
Escherichia coli is a common commensal bacterial species of humans and animals that may become a troublesome pathogen causing serious diseases. The aim of this study was to characterize the quinolone resistance phenotypes and genotypes in E. coli isolates of different origin from one area of the Czech Republic. E. coli isolates were obtained from hospitalized patients and outpatients, chicken farms, retailed turkeys, rooks wintering in the area and wastewaters. Susceptibility of the isolates grown on the MacConkey agar with ciprofloxacin (0.05 mg/L) to 23 antimicrobial agents was determined. The presence of plasmid-mediated quinolone resistance (PMQR) and ESBL genes was tested by PCR and sequencing. Specific mutations in gyrA, gyrB, parC and parE were also examined. Multilocus sequence typing and pulsed-field gel electrophoresis were performed to assess the clonal relationship. In total, 1050 E. coli isolates were obtained, including 303 isolates from humans, 156 from chickens, 105 from turkeys, 114 from the rooks and 372 from wastewater samples. PMQR genes were detected in 262 (25%) isolates. The highest occurrence was observed in isolates from retailed turkey (49% of the isolates were positive) and inpatients (32%). The qnrS1 gene was the most common PMQR determinant identified in 146 (56%) followed by aac(6´)-Ib-cr in 77 (29%), qnrB19 in 41 (16%) and qnrB1 in 9 (3%) isolates. All isolates with high level of ciprofloxacin resistance (>32 mg/L) carried double or triple mutations in gyrA combined with single or double mutations in parC. The most frequently identified substitutions were Ser(83)Leu; Asp(87)Asn in GyrA, together with Ser(80)Ile or Glu(84)Val in ParC. Majority of these isolates showed resistance to beta-lactams and multiresistance phenotype was found in 95% isolates. Forty-eight different sequence types among 144 isolates analyzed were found, including five major clones ST131 (26), ST355 (19), ST48 (13), ST95 (10) and ST10 (5). No isolates sharing 100% relatedness and originating from different areas were identified. In conclusion, our study identified PMQR genes in E. coli isolates in all areas studied, including highly virulent multiresistant clones such as ST131 producing CTX-M-15 beta-lactamase.